2008
DOI: 10.1016/j.molcel.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Smc3 by Eco1 Is Required for S Phase Sister Chromatid Cohesion in Both Human and Yeast

Abstract: Sister chromatid cohesion is normally established in S phase in a process that depends on the cohesion establishment factor Eco1, a conserved acetyltransferase. However, due to the lack of known in vivo substrates, how Eco1 regulates cohesion is not understood. Here we report that yeast Eco1 and its human ortholog, ESCO1, both acetylate Smc3, a component of the cohesin complex that physically holds the sister chromatid together, at two conserved lysine residues. Mutating these lysine residues to a nonacetylata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
397
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(425 citation statements)
references
References 17 publications
16
397
2
3
Order By: Relevance
“…Early studies had pointed out the involvement of a specialized class of acetyltransferases (Eco1/Ctf7 in budding yeast; ESCO1 and ESCO2 in vertebrates) (Ivanov et al 2002;Bellows et al 2003). A series of subsequent studies showed that two conserved residues in SMC3 are the essential targets of the Eco1/ESCO1 acetyltransferase, and the acetylation reactions are indeed essential for cohesion establishment in budding yeast (Ben-Shahar et al 2008;Unal et al 2008) and humans (Zhang et al 2008). More recently, the deacetylase that reverses this reaction has been identified as Hos1 in budding yeast (Beckouët et al 2010;Borges et al 2010;Xiong et al 2010) and HDAC8 in humans (Deardorff et al 2012).…”
Section: Cohesin Establishes Sister Chromatid Cohesion During S Phasementioning
confidence: 99%
“…Early studies had pointed out the involvement of a specialized class of acetyltransferases (Eco1/Ctf7 in budding yeast; ESCO1 and ESCO2 in vertebrates) (Ivanov et al 2002;Bellows et al 2003). A series of subsequent studies showed that two conserved residues in SMC3 are the essential targets of the Eco1/ESCO1 acetyltransferase, and the acetylation reactions are indeed essential for cohesion establishment in budding yeast (Ben-Shahar et al 2008;Unal et al 2008) and humans (Zhang et al 2008). More recently, the deacetylase that reverses this reaction has been identified as Hos1 in budding yeast (Beckouët et al 2010;Borges et al 2010;Xiong et al 2010) and HDAC8 in humans (Deardorff et al 2012).…”
Section: Cohesin Establishes Sister Chromatid Cohesion During S Phasementioning
confidence: 99%
“…An antiestablishment complex consisting of Wings Apart-Like protein (WAPL)/Rad61 and Pds5 is required to maintain cohesion during G2/M by stabilizing the interaction between cohesin and the chromosomes (Panizza et al, 2000;Losada et al, 2005;Gandhi et al, 2006). While the specific details of how Ctf7, WAPL/Rad61, and Pds5 function together to first establish and then maintain cohesion still need to be clarified, recent results indicate that Ctf7 acetylates conserved Lys residues in SMC3, which inhibits the antiestablishment function of the Wpl1-Pds5 complex and promotes cohesion establishment (Ben-Shahar et al, 2008;Unal et al, 2008;Zhang et al, 2008;Rowland et al, 2009;Sutani et al, 2009). Ctf7 is also involved in the postreplicative induction of cohesion induced by DNA double-strand breaks (Unal et al, 2007).…”
mentioning
confidence: 99%
“…wapl1-1 wapl2 plants appear relatively normal but exhibit defects in both male and female meiosis (De et al, 2014). Also similar to the situation in yeast (Rolef Ben-Shahar et al, 2008;Unal et al, 2008;Zhang et al, 2008;Rowland et al, 2009;Sutani et al, 2009), inactivation of WAPL suppresses the lethality associated with ctf7 mutations in Arabidopsis (De et al, 2014). wapl1-1 wapl2 ctf7 plants are obtained at expected rates, display normal growth and development, and produce small numbers of viable seed.…”
Section: Discussionmentioning
confidence: 66%
“…Prior to S phase, cohesin binding to the chromosomes is dynamic and is regulated by a complex containing the Wings apart-like (Wapl) and Precocious Dissociation of Sisters 5 (Pds5) proteins, which have been termed the releasing or antiestablishment complexes (Gandhi et al, 2006;Gerlich et al, 2006;Kueng et al, 2006;Rolef Ben-Shahar et al, 2008;Rowland et al, 2009;Sutani et al, 2009;Ouyang et al, 2013). The establishment of cohesion, which occurs during S phase (Skibbens et al, 1999;Tóth et al, 1999), is facilitated by acetylation of two adjacent lysine residues on SMC3 by the Ctf7 (Chromosome Transmission Fidelity7)/Eco1 acetyltransferase (Rolef Ben-Shahar et al, 2008;Unal et al, 2008;Zhang et al, 2008;Rowland et al, 2009). This modification of the cohesin complex appears to antagonize the action of the Wapl-Pds5 complex and to stabilize the association of cohesin with the chromatin (Rolef Ben-Shahar et al, 2008;Unal et al, 2008;Zhang et al, 2008;Rowland et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation